10 Katlı Çelik Bir Ofis Binasının Boyutlandırılması Ve İlerlemeli Çökme Analizi - Şehirali, Ahmet Serdar (Fen Bilimleri Enstitüsü, 2012)
Yüksek lisans tezi olarak sunulan bu çalışmada, 10 katlı bir ofis binasının TS 648 ve DBYBHY 2007’ye göre boyutlandırılması yapılmış olup, Amerikan Savunma Bakanlığı’nın UFC 4-023-03 kıstasına göre ilerlemeli çökmeye karşı davranışı incelenmiştir. Tezin ilerlemeli çökme analizi ile ilgili kısımları Almanya’da Hamburg Teknik Üniversitesi’nde yürütülmüş diğer kısımlar İTÜ’de çalışılmıştır. İlk bölümlerde yapının boyutlandırılması üzerinde durulmuştur. Yapı normal süneklik özelliği gösteren, kompozit döşeme sisteminde teşkil edilen ve genel hatlarıyla rijit çerçevelerden oluşan bir yapıdır. Döşeme kirişleri IPE 270, kat kirişleri HE 450B, kolonlar ise HE 600B ve HE 700M profilleri kullanılarak boyutlandırılmıştır. Döşeme kirişlerinin kompozit kiriş olarak boyutlandırılırsa IPE 270, basit kiriş olarak boyutlandırılırsa IPE 330 profili kullanılması gerektiği sonucuna varılmış bu nedenle daha ekonomik olan kompozit döşeme sistemi yapı için seçilmiştir. Döşeme kirişi ile kat kirişi birleşimlerinde yüksek mukavemetli bulonlu birleşimler tercih edilmiştir. Kat kirişi ile kolonların mafsallı birleşimlerinde gene yüksek mukavemetli bulonlu birleşimler ancak rijit birleşimlerinde ise kaynaklı birleşimler tercih edilmiştir. Kolon eklerinde öngerilmeli yüksek mukavemetli bulonlar kullanılmıştır. Ankastre kolon ayaklarında ise uygun ve yeter miktarda ankraj bulonları kullanılmış olup bunların temele bağlantısı ankraj profilleri ile sağlanmıştır. İlerlemeli çökmeye karşı yapının incelenmesi ile ilgili çalışmanın teorisi ve uygulaması ilerleyen bölümlerde anlatılmıştır. İlerlemeli çökmenin öneminden bahsedilmiş, uygulanması gereken yollar ve seçilecek analiz prosedürleri açıklanmıştır. Ayrıca yapıya uygulanması gereken yeni yüklerin hesabı anlatılmıştır. Yapının ilerlemeli çökmeye karşı yeniden dizaynının gerekli olup olmadığı incelenmiştir. Yapının, herhangi bir köşesinde veya kenarında, iki veya üç kolon ardı ardına, herhangi bir dış etken nedeni ile (patlama, çarpma vs.) yıkılırsa, yapının ilerlemeli çökmeye başlayacağı, ancak tekli kolon yıkılmalarında yapının güvenli bir şekilde ayakta kalmaya devam edeceği, sonuçlarına varılmıştır. Eğer yapı ilerlemeli çökmeye karşı yeniden dizayn edilecekse bu durumun göz önüne alınması gerektiği üzerine durulmuştur. Ancak bu çalışmada, tekli kolon yıkılmalarına karşı binanın ayakta kalma kabiliyeti yeterli görülmüş ve yapı yeniden dizayn edilmemiştir. Kuşkusuz, kolon ve kiriş kesitleri arttırılarak yapının daha rijit bir hale getirilmesi sonucu yıkımların önüne geçmek mümkündür. Belki ekonomik açıdan olumlu sonuçlar alınmayacak fakat daha da önemli olan olası can kayıpları mümkün olduğunca önlenmiş olacaktır.

In this paper which is presented as a M.Sc thesis, a 10 storey office building is designed and sized by using Turkish Standart TS 648 and Design Specifications for Buildings in Earthquake Regions (DBYBHY 2007). Then a special attention on disproportionate collapse is highlighted and the structure is examined for a necessity of a redesign against progressive collapse according to the Unified Facilities Criteria (UFC 4-023-03). Sections which examined progressive collapse analysis are studied at Technical University of Hamburg in Germany while the remaining sections that examined preliminary design and sizing of the structural elements are studied at Istanbul Technical University. In the 1st section, the detailed structural model descriptions are given. The structural model has a normal ductility level with a composit slab system. Outer of the structural model has Moment-Frames in both directions x and y but on the other hand, the layouts of the columns varies inner of the structure as their strong and weak axis direction changes. They are disposed to cover the lateral loads for both directions x and y so that the structure could be able to show its ductility and amortization for both direction without any necessity of braces. That design is preferred for better construction duration and better labor cost which obviously means better economical results. And finally in section 1, the material definitions and Earthquake Characteristic of the model is highlighted. In the 2nd section, the vertical and lateral loads which effects to the structural model is analyzed according to the Turkish Standart TS 498 and the distribution of the loads on the structure is remarked. As a result of the calculations, on the attic floor, the deads loads affected on the unit area are higher than normal floors considering the high level insulation and frameworks. Beam and column weights are added to the dead loads whereas the partition wall weights are added to the live loads so that the structural model weight is taken zero on SAP 2000 during the structural analysis. Additionally, Equivalent Earthquake Force Analysis is runned to calculate the Earthquake Forces and Base Shear Forces are calculated in both direction x and y. Equivalent Earthquake Forces subjected to the floor levels are modeled as single loads affected on the center of the rigid-diaphragms on SAP 2000 model file while wind loads are modeled as distributed loads. Section 2 is finalized with the system analysis results where deformation results, relative interstory drifts and P-Delta effects are found under the required limits. In the 3rd section, the preliminary design and sizing of the structural elements are given. Secondary beams are designed using IPE 270 sections while primary beams are chosen as HE 450B beams and columns are assigned as HE 700M and HE 600B profiles depending on the decrease of the lateral forces related to the elevation. IPE 270 is required for composite beams where IPE 330 is calculated for simple beam design so composite slab system is chosen for the structure for better economical results. In the 4th section, the connection details and foundation calculations are given. As a result of the calculations, high strength bolts are preferred on primary-secondary beam and primary beam-column pinned connections whereby DBYBHY 2007 based full-penetrated welds are used on rigid connections. In addition to these, on column-column joints, prestressed high strength bolts are preferred while anchoring bolts are used on fixed column legs which connects the columns to the soil. Turkish Standart TS 500 is used for soil engineering and a 1.5 meters foundation depth is calculated for the structure to stand in safe. In the 5th section, the theory for the progressive collapse design is given with a direct translation from UFC 4-023-03. The significance of progressive collapse, design approaches and loading procedures are highlighted. In the 6th and the final section, any necessity of a redesign of the model against Progressive Collapse is examined. In accordance with the 5th section, building’s Occupancy Category is taken as OC II Option 2 and Alternate Path Method is used as design procedure. This design method is chosen because the aim is to determine if the structure can bridge over the deficient element after it has been notionally removed. Additionally, Nonlinear Dynamic Analysis Procedure is chosen for Progressive Collapse Analysis to find the most precise result and to neglect Load Increase Factor calculation. During the Progressive Collapse Analysis, first of all, 4 columns are removed individually from the structure to examine the collapse behaviour, but in the end, on the removed element locations, the maximum displacements are reached and the oscillations are damped by the structure and no collapse has occured. And then, the same 4 columns are removed simultaneously from the structure to examine the collapse behaviour once again but again no collapse has occured and the structure continued to stand still. Finally, apart from the other columns, another random chosen column is removed from the edge of the structure, but this time, in contrast to the others, the structure has collapsed at last. The structure couldn’t correspond a 25m bay on its edge and the plastic hinges passed collapse prevention limit, as a result, it started to collapse progressively. The collapse mechanicism of the structure is assumed to be in zipper type. It is called as an assumption because this progression could last until the structure collapse totally or could stop on the middle part of the structure which was seen in real life on Oklohama City Bombing and in many cases. The collapse mechanicism of the structure is surely a separate field of study. To summarize all, if an explosion or impact appears on any corner of the structure which is caused by a terrorist attact or similar effects 2-3 consecutive columns at once, the structure would collapse. Theorically, this result can be generalized for any corner of the building because the structure is symmetrical and it would give the same response in every corner. In this study, the structure isn’t redesigned because structure’s bridging over against individual column removal satisfied the aim of the M.Sc thesis. It is obvious that strengthening the sections will increase the structure’s rigidity to correspond the collapse in a better way. Surely, this won’t be as economical as the owner’s want but will save lots of civilian casualities.
Design Of A 10 Storey Office Building With Special Attention On Progressive Collapse Analysis
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2011
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2011
Keywords: İlerlemeli Çökme; 10 Katlı Çelik Ofis Binası; TS648; DBYBHY 2007; UFC 4; Progressive Collapse; 10 Storey Office Building; TS648; DBYBHY 2007; UFC 4